2022
DOI: 10.3390/jcm11092411
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Is a Major Symptom at COVID-19 Hospitalization Follow-Up

Abstract: Persistent symptoms after hospitalization with COVID-19 are common, but the frequency and severity of these symptoms are insufficiently understood. We aimed to describe symptoms and pulmonary function after hospitalization with COVID-19. Patients hospitalized with COVID-19 in Central Denmark Region were invited for follow-up 3 months after discharge. Clinical characteristics, patient reported outcomes (Fatigue Assessment Scale (FAS), anxiety and depression (HADS)), symptoms, pulmonary function test and 6-min w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
12
0
3
Order By: Relevance
“…Post-COVID-19 is referred to as “the decrease in physical and/or mental performance that results from changes in central, psychological, and/or peripheral factors due to the COVID-19 disease” 5 . Previous literature shows that the prevalence of fatigue was 52% at 10 weeks 6 , 13–47% at 16–20 weeks 7 , 8 and 10–35% at 6 months 7 after COVID-19. The prevalence of post-COVID-19 fatigue was much higher in hospitalized individuals, with 36–53% reporting fatigue soon after the recovery from acute symptoms 9 , 10 , 26% at 3 months 11 , 63% at 6 months 12 and 20% at 1 year 13 after discharge from the hospital.…”
Section: Introductionmentioning
confidence: 88%
“…Post-COVID-19 is referred to as “the decrease in physical and/or mental performance that results from changes in central, psychological, and/or peripheral factors due to the COVID-19 disease” 5 . Previous literature shows that the prevalence of fatigue was 52% at 10 weeks 6 , 13–47% at 16–20 weeks 7 , 8 and 10–35% at 6 months 7 after COVID-19. The prevalence of post-COVID-19 fatigue was much higher in hospitalized individuals, with 36–53% reporting fatigue soon after the recovery from acute symptoms 9 , 10 , 26% at 3 months 11 , 63% at 6 months 12 and 20% at 1 year 13 after discharge from the hospital.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study, we examined symptoms using validated patient-reported outcome measures (PROMs) and objective outcomes, e.g., pulmonary function tests (PFT) and 6-minute walk test (6MWT) 3 months after hospitalization [10] . Fatigue measured by the Fatigue Assessment Scale (FAS) was a major complaint at follow-up, affecting 65% of patients of whom 18% reported severe fatigue [10] , in keeping with several other studies [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Were antibodies against acetylcholine receptors or antibodies against musclespecific kinase positive in any of the included patients? Fatigue in post-COVID patients may be due not only to muscle involvement but also to cerebral involvement in the acute infection [5]. We should be told how many of the enrolled patients had clinical signs of central nervous system (CNS) involvement and how many showed cerebral magnetic resonance imaging CNS pathology that could explain fatigue.…”
Section: Post-covid Myopathymentioning
confidence: 99%